Bombyx Mori as a Potential Sunscreen to Prevent Photoaging - Arnylia Djunaidy; Putu Ayu Asri Damayanti (Jurnal Penelitian Pendidikan IPA, 2023)
Excessive exposure to solar UV radiation is a major cause of skin photoaging, which is characterized by premature wrinkling, hyperpigmentation, and loss of skin elasticity. Traditional synthetic sunscreens are effective, but their potential side effects have led to a search for natural alternatives. Bombyx mori has attracted attention for its rich composition of bioactive compounds, such as silk proteins, sericin and fibroin, which have antioxidant and anti-inflammatory properties. These components are believed to contribute to the protection of skin cells against oxidative stress and inflammation from UV rays, thereby slowing down the aging process. This review systematically examines recent studies that have investigated the photoprotective effects of Bombyx mori-derived extracts, silk proteins, and other related substances. Findings suggest that these natural agents have the potential to reduce UV damage by enhancing skin defense mechanisms, promoting collagen synthesis, and reducing matrix metalloproteinase expression. In addition, the hypoallergenic properties of Bombyx mori compounds make them suitable for individuals with sensitive skin, thereby expanding their application in the skin care industry. However, while promising, research on Bombyx mori as a sunscreen agent is still in its early stages. Further studies are needed to elucidate the mechanisms underlying their photoprotective effects, assess their long-term safety, and optimize their formulations for effective delivery to the skin. This literature review contributes to a comprehensive understanding of the potential of Bombyx mori as an alternative to natural sunscreens and highlights the need for further research in harnessing its benefits to fight photoaging and maintain healthy skin.